Impact of KVK Activities on Sustainable Rural Livelihood of Farmers - Rathod, M K (Journal of Agricultural Extension Management, 2019)
The present study was conducted in Wardha district for evaluation of Krishi Vigyan Kendra (KVK) activities to ascertain the impact on Sustainable Rural Livelihood (SRL) of farmers. The results revealed that the farmers who were engaged only in traditional farming system before involvement in KVK activities then tried different fanning systems like sericulture, livestock, horticulture, apiculture etc. due to the need based and multidisciplinary approach pursued by the KVK. The core indicators of SRL i.e. human capital, physical capital, social capital, financial capital and food security significantly increased over a period of time because of KVK activities. Overall 40.27 per cent increase was recorded which was a highly significant change.